Aplikasi Sistem Monitoring Pertumbuhan Tanaman Berbasis Web Menggunakan Machine Vision - Lilik Sutiarso; Atris Suyantohadi; Dody Kastono; Andri Prima Nugroho (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Nowadays, demand for integrating between information technology (IT) and development of agricultural system isin order to increase the productivity, efficiency and profitability in term of precision agriculture. This matter occurred due to some problems in the field, such as; unintensively monitoring activities for plant during the growing period. One of the alternative solutions to overcome the problem was introducing the machine vision technology in the farming system. The research is actually as a basic research that aims using technology of digital image processing and software of computation (mathematics) to support a function of real-time monitoring system for plant growing. The research mechanism was started from digital image processing by using an image segmentation method that can identify between the main object (plant) and others (soil, weed). Image processing algorithm used excess color method and color normalization to identify plants, to calculate crop area. Otsu method was used to convert it to binary images. The next was to calculate and analyze a percentage of the plant growing, from after planting until harvesting time. The analyzed data were stored as MySQL database format in the web server. Final output of the research was the web based monitoring instruments for plant growing that can be accessed through intranet (local area network) as well as internet technology. From the software testing, monitoring with a machine vision system has a success rate reached 70 % for identifying plants.ABSTRAKTuntutan integrasi teknologi sistem informasi dan sistem pertanian saat ini dimaksudkan guna mendukung efisiensi,produktivitas dan profitabiltas pertanian. Hal tersebut didorong oleh timbulnya permasalahan di lapangan terkait dengan belum optimalnya produktivitas tanaman yang diakibatkan antara lain, kurang intensifnya pemantauan (monitoring) tanaman pada masa pertumbuhan. Salah satu alternatif solusi untuk memperbaiki permasalahan tersebut dengan mengaplikasikan teknologi machine vision. Penelitian yang dilakukan merupakan penelitian dasar yang bertujuan memanfaatkan teknologi pengolahan citra digital dan perangkat lunak komputasi untuk mendukung fungsi monitoring pertumbuhan tanaman secara real-time. Mekanisme penelitian dimulai dengan tahap pengolahan citra digital yang menggunakan metode segmentasi untuk mengenali objek tanaman dengan objek lainnya. Algoritma pengolahan citra menggunakan metode kelebihan hijau dan normalisasi warna, sedangkan untuk menghitung luas tanaman digunakan metode Otsu dengan mengubah ke citra biner. Tahap berikutnya menghitung prosentase pertumbuhan tanaman selama proses budidaya sampai dengan panen. Data hasil pencitraan disimpan dalam basisdata MySql. Hasil akhir dari pengolahan data ditampilkan sebagai informasi pertumbuhan tanaman yang ditampilkan di website. Dari hasil pengujian, sistem monitoring dengan machine vision ini memiliki tingkat keberhasilan mencapai 70 % dalam mengenali tanaman.